Evaluation of the adequacy of infant formula labeling - Lôbo Bezerra de Albuquerque, Gabriela; Batista da Silva, Elga; Rodrigues, Nathália; Toste Cardoso, Fabiane (O Mundo da Saúde, 2016)
Human breast milk is the best food option for children up to one year of age, but in cases with contraindication or for mothers who, for some reason cannot breast-feed their infants, formulas are indicated because they are especially modified to meet the physiological and nutritional needs in this age group. The aim of this work was to analyze infant formula labeling, marketed in the city of Rio de Janeiro, according Brazilian law. A total of 23 formulas were analyzed based on 19 items to verify the conformity of the labels, based on norms established by the Brazilian Ministry of Health. It was observed that among the items evaluated under the current legislation 45% presented inadequacies. The presence of false concepts of advantage and security (21.7%) and health claims (17.4%) were also among those with the highest number of nonconformities. The results evidenced the need for: 1) children’s formula companies (for the ones who are under one year) to match their product labels to relevant legislation; 2) sanitary organs to monitor the labels of infant formulas more effectively.